Analisis Komparatif Metode Rasio Keuangan dan Economic Value Added (Eva) untuk Menilai Kinerja Keuangan Perusahaan (Studi pada PT. Sumber Alfaria Trijaya, Tbk dan PT. Indofood Sukses Makmur, Tbk yang terdaftar di BEI Periode Tahun 2019-2020) - Atti Rasnawati; Ade Jermawinsyah (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
This study raises the issue of comparative financial ratio calculations consisting of liquidity ratios (current ratio, Quik ratio and cash ratio), leverage ratios (debt ratio and debt equation ratio), Activity ratios (TATO and FATO) as well as Profitability Ratios (GPM, OPM, NPM, ROI and ROE) as well as the Economic Value Added (Eva) method in companies listed on the Indonesia Stock Exchange (IDX), namely PT. Source Alfaria Trijaya, Tbk and Indofood Sukses Makmur Tbk. The purpose of this study is to analyze and compare the financial performance of the two companies using the financial ratio method and the Economic Value Added (Eva) method. the results of this study the calculation of financial ratios shows positive results in each ratio and each company, the results of calculations using the Economic Value Added (EVA) method have shown the occurrence of economic added value for the two companies, the comparison of the results is PT. Indofood Sukses Makmur Tbk has a greater value than PT. Sumber Alfaria Trijaya, Tbk in this case both have positive values.